Prontuário eletrônico como recurso pedagógico para os cursos de saúde - Melo Neto, Newton de Barros (2020)
The Academic Work for Course Completion (AWCC) aimed to evaluate the use of the Electronic Medical Record (EMR) as a pedagogical resource. The methodology used was quantitative, through the application of a structured and previously validated questionnaire, containing closed and open questions, addressing satisfaction with the EMR implemented in the service, the evaluation of this tool as a pedagogical resource and the involvement in the teaching-learning process. 110 residents participated in the research, 70 from the medical residency program and 40 from the multiprofissional residency program. The results of the research are presented in an original article entitled: Electronic Health Record as a Pedagogical Resource: Perception of Residents of a University Hospital. Most of the residents were female, graduated from public institutions between 2003 and 2019, with an average age of 28 years, this profile made it possible to classify the participants as a generation with mastery of technological resources, called generation Y. When analyzing familiarity with the EMR, 44.5% stated that the first contact with this tool occurred only at home and 90.9% claimed that during graduation no discipline worked with the EMR. Residents recognized the relevance of the information generated in the EMR to the learning process and the importance of being used as a teaching tool. It is concluded that it is necessary to develop the students' digital competence, so that they can have a critical and reflective look at the electronic records, and for that, the EMR needs to be recognized and adopted by teachers as a pedagogical resource. The identification of gaps in the adoption of the EMR in the learning process in health courses, led to the development of two intervention products: the creation of an electronic application, in the form of a prototype, called "electronic learning record", to be used in undergraduate courses as an interactive platform between teachers, students and preceptors and the production of an explanatory video directed to teachers, addressing the importance of EMR in the practice scenario and the possibilities of use as a pedagogical resource.